JAVANESE CULINARY GLOCALIZATION THROUGH LEARNING INDONESIAN - Ananda Ainun; Anita Marta Zohriyah; Umi Nur Sholikhah; Hanifah Nurul Isnaini; Fajar Rizki Apriyanto (Vol. 2 No. 1 (2024): Proceeding of International Conference on Cultures & Language 2024, 2024)
Language is a communication tool that reflects the identity, values and traditions of a society. In the culinary context, language plays an important role in explaining and understanding various aspects of cooking. Culinary refers to everything related to food and drink, including the process of cooking, serving, and consuming food. The purpose of this research is to uncover traditional culinary in Language Education and appreciation of Indonesian culinary wealth. The method used is descriptive qualitative with content analysis strategy and literature analysis. From this research it has been found that the role of culinary as a tool to develop Indonesian learning materials is about adapting more locally recognized terms to introduce traditional dishes to the Indonesian people. This is done so that people can more easily understand and accept various types of traditional food by using a more familiar language. This process helps to strengthen local cultural identity while promoting Indonesia's culinary heritage to foreigners.